EFEKTIVITAS PEMBELAJARAN BERBASIS STUDENT CENTERED LEARNING DALAM MENGATASI KECEMASAN KOMUNIKASI - Yohanes Wendelinus Dasor (PGSD UNIKA SANTU PAULUS RUTENG, 2017)
Communication anxiety is commonly experienced by human being. Anxiety is the emotion characterized by an unpleasant state of inner turmoil, often by nervous behavior. Itis, however, a threat which impedes and affects individuals in building quality of communication with others. Anxiety may also occur to a personin interpersonal communication. Therefore, it should be well treated by encouraging the students’ bravery in communication. Student-centered learning (SCL) is a cooperative learning which emphasizes the students’ participation and engagement in learning process. By this method, the learners are able to develop their character and self-efficacy in performing public communication.